2022
DOI: 10.3390/jcm11040993
|View full text |Cite
|
Sign up to set email alerts
|

Neurostimulation in People with Oropharyngeal Dysphagia: A Systematic Review and Meta-Analysis of Randomised Controlled Trials—Part II: Brain Neurostimulation

Abstract: Objective. To assess the effects of brain neurostimulation (i.e., repetitive transcranial magnetic stimulation [rTMS] and transcranial direct current stimulation [tDCS]) in people with oropharyngeal dysphagia (OD). Methods. Systematic literature searches were conducted in four electronic databases (CINAHL, Embase, PsycINFO, and PubMed) to retrieve randomised controlled trials (RCTs) only. Using the Revised Cochrane risk-of-bias tool for randomised trials (RoB 2), the methodological quality of included studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 70 publications
0
19
0
1
Order By: Relevance
“…Although there is no clear evidence of superiority of one NIBS technique over the other, the effects of rTMS seem to be greater than those of tDCS [101,100 ▪▪ ]. Anyway, among the strengths of tDCS, there are greater accessibility to treatment and possibility of home therapy, thanks to portable devices.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Although there is no clear evidence of superiority of one NIBS technique over the other, the effects of rTMS seem to be greater than those of tDCS [101,100 ▪▪ ]. Anyway, among the strengths of tDCS, there are greater accessibility to treatment and possibility of home therapy, thanks to portable devices.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“… 92 , 93 In dysphagic patients, particularly stroke patients, a large number of RCTs on the effects of these NIBS techniques on swallowing have been published in the last decade. 78 , 94 Overall, although there is substantial variability in stimulation parameters and no consensus has been reached as regards the optimal stimulation protocol, NIBS techniques have shown preliminary treatment benefits for patients with post-stroke dysphagia. Importantly, Cheng et al analysed the effects of neuromodulation treatments based on the timing of follow-ups.…”
Section: Neuromodulation Treatmentsmentioning
confidence: 99%
“…Over the last two decades, a number of randomized controlled trials (RCTs) have been conducted to explore the therapeutic value of rTMS for the treatment of dysphagia (Table 1). Recent systematic reviews and meta-analyses suggested that rTMS may have potential benefits for neurogenic dysphagia [35,36]. However, the stimulation protocol, in particular the stimulation hemisphere and frequency, remains the centre of debate for rTMS treatments.…”
Section: Neurogenic Dysphagia (Stroke) Studiesmentioning
confidence: 99%